Negative Emotions’ Impact on Consumer Satisfaction and Loyalty Due to Failures in Financial Services: Application of the Affective-Cognitive Model; [Impacto de Las Emociones Negativas en la Satisfacción y Lealtad del Consumidor Debido a Fallas en Los Servicios Financieros: Aplicación del Modelo Afectivo-Cognitivo] - Ponce-Arias, H (Emerald Publishing, 2025)
Purpose: We examine negative emotions’ influence on consumer satisfaction and loyalty when repurchasing a product or service after experiencing failures in the financial services sector. Design/methodology/approach: The sample comprised 735 valid surveys of customers who encountered such service failures. An initial model incorporating 14 negative emotions was narrowed down to the most robust one, comprising three emotions, after data collection and statistical validation. Findings: Consumer dissatisfaction is explained by affective (pleasure) rather than cognitive factors (disconfirmation) in the financial services context. Loyalty is influenced only by affective (pleasure and activation) rather than cognitive elements (disconfirmation) in the dissatisfaction generation process, indicating that loyalty is not a cognitive but an affective one. Finally, an affective judgment (activation) rather than a cognitive one (disconfirmation) explains consumer’s recommendation of a product or service despite encountering failures. Originality/value: This is the first study to focus exclusively on negative emotions, revealing that the pleasure dimension is a significant antecedent of dissatisfaction. By demonstrating that emotional factors rather than cognitive assessments dominate both satisfaction and loyalty responses, this study offers a unique contribution to understanding consumer behavior after service failures in financial services, with practical implications for service recovery strategies. © 2024, Emerald Publishing Limited.